Rainfall measurement using cell phone links: classification of wet and dry periods using geostationary satellites. Issue 9 (4th July 2017) - van het Schip, T. I.; Overeem, A.; Leijnse, H.; Uijlenhoet, R.; Meirink, J. F.; van Delden, A. J.
ABSTRACT: Commercial cellular telecommunication networks can be used for rainfall estimation by measuring the attenuation of electromagnetic signals transmitted between antennas from microwave links. However, as the received link signal may also decrease during dry periods, a method to separate wet and dry periods is required. Methods utilizing ground-based radar rainfall intensities or nearby link data cannot always be used. Geostationary satellites can provide a good alternative. A combination of two Meteosat Second Generation satellite precipitation products, Precipitating Clouds and Cloud Physical Properties, is employed to decide whether a 15-min time interval for a given link is rainy or not. A 12-d dataset of link-based rainfall maps for the Netherlands is validated against gauge-adjusted radar rainfall maps. Results clearly improve upon the case when no wet–dry classification is applied and thus the method shows potential for application to large areas of the world where the other methods cannot be applied.